Neoadjuvant camrelizumab plus chemotherapy for locally advanced cervical cancer (NACI Study): a study protocol of a prospective, single-arm, phase II trial - Jing Chen; Gang Chen; Kezhen Li; YingJie Hu; Chaoyang Sun; Yingyan Han; Xue Feng; Xiaolin Meng; Shuaiqingying Guo (BMJ Open, 2023)
Introduction Neoadjuvant chemotherapy (NACT) is an emerging approach for locally advanced cervical cancer (LACC). However, the clinical response and postoperative adjuvant radiation or chemoradiation trimodality treatment resulted in controversy. PD-1 inhibitors have shown promising role in recurrent or metastatic cervical cancer, and there is preclinical evidence of the activation and synergistic effects of NACT on PD-1 inhibitors. This study aims to evaluate the efficacy and safety of the preoperative PD-1 inhibitor camrelizumab combined with NACT for LACC.Methods and analysis The study is designed as a multicentre, open-label, single-arm, prospective phase II study. A total of 82 patients will receive neoadjuvant chemo-immunotherapy, defined as one cycle of cisplatin (75–80 mg/m2, intravenously) plus nab-paclitaxel (260 mg/m2, intravenously) NACT and subsequent two cycles of camrelizumab (200 mg, intravenously) combined with NACT. After neoadjuvant chemo-immunotherapy, patients exhibiting complete response and partial response will undergo radical surgery and subsequent adjuvant therapy. In contrast, patients with stable disease and progressive disease will transfer to concurrent chemoradiotherapy (CCRT). Following surgery, patients will receive adjuvant CCRT or radiotherapy. The primary endpoint is the objective response rate. The secondary endpoints are the pathological complete response, patients requiring postoperative adjuvant therapy, safety of neoadjuvant chemo-immunotherapy, surgical complication, event-free survival, and overall survival. An additional aim is to dynamically evaluate peripheral immune responses and local immunological microenvironments and their association with neoadjuvant immunotherapy.Ethics and dissemination This trial was approved by the Medical Ethics Committee of Tongji Medical College, Huazhong University of Science and Technology (S2020-112). This study is among the first to evaluate the efficacy and safety of neoadjuvant chemo-immunotherapy in LACC. The findings of this research will promote neoadjuvant anti-PD-1 immunotherapy with radical surgery as a new therapeutic strategy.Trial registration number ClinicalTrials.gov Registry (NCT04516616).